2022
DOI: 10.3390/nano12203682
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Two Phases in Li4SiO4–Li2SiO3 Ceramics on the Strength and Thermophysical Parameters

Abstract: The paper studies the effect of Li2SiO3/Li4SiO4 phase formation in lithium-containing ceramics on the strength and thermophysical characteristics of lithium-containing ceramics, which have great prospects for use as blanket materials for tritium propagation. During the phase composition analysis of the studied ceramics using the X-ray diffraction method, it was found that an increase in the lithium component during synthesis leads to the formation of an additional orthorhombic Li2SiO3 phase, and the main phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In the case when the Li 4 SiO 4 phase prevails in the composition of ceramics, the composition is dominated by small-sized grains, completely hiding the Li 2 TiO 3 grains. In summary, having analyzed the data on the morphological features of the obtained grains, we can conclude that the change in the ratio of Li 2 TiO 3 /Li 4 SiO 4 components leads to the formation of ceramics with different geometric grain sizes, which can play an important role in determining the strength characteristics, as it was shown in [30,31] that the transition to the fine-grained fraction of ceramics has a significant effect on the resistance to radiation damage during the accumulation of nuclear reaction products and also increases the stability of ceramics to external influences.…”
Section: Characterization Of Initial Samples Obtained Using Mechanica...mentioning
confidence: 65%
See 1 more Smart Citation
“…In the case when the Li 4 SiO 4 phase prevails in the composition of ceramics, the composition is dominated by small-sized grains, completely hiding the Li 2 TiO 3 grains. In summary, having analyzed the data on the morphological features of the obtained grains, we can conclude that the change in the ratio of Li 2 TiO 3 /Li 4 SiO 4 components leads to the formation of ceramics with different geometric grain sizes, which can play an important role in determining the strength characteristics, as it was shown in [30,31] that the transition to the fine-grained fraction of ceramics has a significant effect on the resistance to radiation damage during the accumulation of nuclear reaction products and also increases the stability of ceramics to external influences.…”
Section: Characterization Of Initial Samples Obtained Using Mechanica...mentioning
confidence: 65%
“…As can be seen from the presented data comparing hardness values and resistance to single compression (i.e., the maximum amount of pressure the ceramics can withstand when compressed at a constant rate of 5 mm/min), Li 4 SiO 4 ceramics have higher strength characteristics than Li 2 TiO 3 ceramics in the case of single-component ceramics. This difference can be explained by both dimensional factors (for Li 2 TiO 3 , the grain sizes are much larger than for Li 4 SiO 4 ceramics, which leads to a lower dislocation density) and structural features of the ceramics (Li 4 SiO 4 ceramics, according to a number of studies have higher strength values [28,[31][32][33]). When varying the ratio of Li 2 TiO 3 /Li 4 SiO 4 components, it was found that an increase in the Li 4 SiO 4 content leads to an increase in hardness and maximum load, the maximum of which is reached in the case of 0.75Li 4 SiO 4 -0.25Li 2 TiO 3 ceramics, for which the increase in hardness in comparison with single-component ceramics amounted to more than 19% and the maximum load more than 15%.…”
Section: Characterization Of Initial Samples Obtained Using Mechanica...mentioning
confidence: 99%
“…Therefore, comprehensive testing and analysis are indispensable for guaranteeing the safety and effectiveness of deploying these materials in fusion reactors [18][19][20]. In the realm of thermonuclear fusion [21,22], a pivotal undertaking is the exploration and advancement of blanket materials that can endure high temperatures and withstand elevated radiation levels without degradation while maintaining their strength properties. The execution of high-temperature tests serves as a crucial means to assess the performance of these materials within a fusion reactor.…”
Section: Introductionmentioning
confidence: 99%